2010
DOI: 10.1007/s00421-010-1511-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal modification of heat-loss responses during exercise in humans

Abstract: This review focuses on the characteristics of heat-loss responses during exercise with respect to non-thermal factors. In addition, the effects of physical training on non-thermal heat-loss responses are discussed. When a subject is already sweating the sweating rate increases at the onset of dynamic exercise without changes in core temperature, while cutaneous vascular conductance (skin blood flow) is temporarily decreased. Although exercise per se does not affect the threshold for the onset of sweating, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 103 publications
(150 reference statements)
0
24
0
Order By: Relevance
“…It is believed that the SR at a given core temperature (thermal input) during exercise is greater than that at rest (e.g., passive heating) because an integrative nonthermal input would increase the SR during exercise in addition to thermal factors (21). Muscle metaboreceptors and mechanoreceptors R732 INTEGRATED CONTROL OF NONTHERMAL SWEATING are known to provide afferent inputs from working muscles, and it has been reported that each reflex can induce sweating independently (20,23,39).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…It is believed that the SR at a given core temperature (thermal input) during exercise is greater than that at rest (e.g., passive heating) because an integrative nonthermal input would increase the SR during exercise in addition to thermal factors (21). Muscle metaboreceptors and mechanoreceptors R732 INTEGRATED CONTROL OF NONTHERMAL SWEATING are known to provide afferent inputs from working muscles, and it has been reported that each reflex can induce sweating independently (20,23,39).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…In a wet, windy environment with an ambient temperature of 5°C, so long as exercise intensity is fairly high, for example, a strong pace of walking, there is no change in core body temperature or rate of energy expenditure compared with thermoneutral conditions (129). Indeed, during periods of man-hauling, sweating and peripheral vasodilation occurs, necessary to dissipate the excess heat produced (60). However, if the work rate is lower, even though this still represents walking at a standard pace (129), core temperature decreases by around 1°C while rate of energy expenditure rises (probably primarily due to shivering; Ref.…”
Section: Polar Temperaturesmentioning
confidence: 99%
“…HUMAN ECCRINE SWEAT GLANDS respond to both thermal and nonthermal drives (26,27), and their secretions serve a wide range of secondary functions, such as facilitating tactile and thermal sensitivity, increasing contact friction (grip), and reducing the risk of tissue damage (55). The main nonthermal drive to sweating in resting individuals is mental stress or arousal, referred to here as psychogenic sweating (32).…”
mentioning
confidence: 99%